EXPERIMENTAL STUDY OF NEPTUNYL ADSORPTION ONTO BACILLUS SUBTILIS - Gorman-Lewis D.; Fein J.B.; Soderholm L.; Jensen M.P.; Chiang M.H. (My University, 2005)
The subsurface mobility of Np is difficult to predict in part due to uncertainties associated with its sorption behavior in geologic systems. In this study, we measured Np adsorption onto a common gram-positive soil bacterium, Bacillus subtilis. We performed batch adsorption experiments with Np(V) solutions as a function of pH, from 2.5 to 8, as a function of total Np concentration from 1.29 × 10−5 M to 2.57 × 10−4 M, and as a function of ionic strength from 0.001 to 0.5 M NaClO4. Under most pH conditions, Np adsorption is reversible and exhibits an inverse relationship with ionic strength, with adsorption increasing with increasing pH. At low pH in the 0.1 M ionic strength systems, we observed irreversible adsorption, which is consistent with reduction of Np(V) to Np(IV). We model the adsorption reaction using a nonelectrostatic surface complexation approach to yield ionic strength dependent NpO2+-bacterial surface stability constants. The data require two bacterial surface complexation reactions to account for the observed adsorption behavior: R-L1− + NpO2+ ↔ R-L1-NpO2° and R-L2− + NpO2+ ↔ R-L2-NpO2°, where R represents the bacterium to which each functional group is attached, and L1 and L2 represent the first and second of four discrete site types on the bacterial surface. Stability constants (log K values) for the L1 and L2 reactions in the 0.001 M system are 2.3 ± 0.3 and 2.3 ± 0.2, and in the 0.1 M system the values are 1.7 ± 0.2 and 1.6 ± 0.2, respectively. The calculated neptunyl-bacterial surface stability constants are not consistent with values predicted using the linear free energy correlation approach from Fein et al. (2001), suggesting that possible unfavorable steric interactions and the low charge of NpO2+ affects Np-bacterial adsorption.